"Dual" drainage in cardiac partial anomalous pulmonary venous return. Issue 5 (13th February 2022) - Sharma, Smily; Das, Anupam; Deora, Surender; Rajagopal, Rengarajan
Abstract: Anomalous drainage of pulmonary veins into the coronary sinus is an uncommon variety of anomalous pulmonary venous return. Rarely, anomalously draining pulmonary veins may show "dual" drainage. We present the imaging findings of an infant who had dual drainage of a cardiac type of partial anomalous pulmonary venous return in the setting of unroofing of the coronary sinus which has not previously been described.